Impact of the Implementation of Broder Crossing Area Agreement between Indonesian and the Philippines at the Border of Miangas Island of North Celebes - Frederik, Wulanmas A.P.G (UI Scholars Hub, 2011)
The existence of Border Crossing Area Agreement (BCA) in 1975 regulating the border agreement between Miangas Island of North Celebes and the Philippines created positive and negative impacts on border people in Miangas Island. The legal aspects, BCA is a legal regulation regulating the border crossing and commerce in that area; economic aspects; BCA has not accommodated border people’s interests maximally yet and it has a limiting impression rather than facilitating people’s interests, thus, illegal trades occur at the border of Miangas Island; social aspects, BCA is hard to implement in this area because it has limited the tradition practicing from generations to generations; political aspects, BCA causes frequent migrations by border people of Miangas Island to the Philippines because of the strong historical and kinship factors, economic factors, to get better education, facilities and infrastructures in health, and communication and transportation that in the Philippines are considered better. These situations made the regional government to use its authority in Act No. 22 of 1999 concerning International Covenant and Act 32 of 2004 concerning Regional Government to empower the Border Crossing Area Agreement in Miangas Island by revising that agreement. The efforts conducted by the government were by issuing the Regional Ordinance No. 1 of 2001 concerning the development of Sangihe and Talaud Islands area and Regional Ordinance No. 2 of 2001 concerning the Spatial Arrangement of Sangihe and Talaud Mainstay Area. It is expected that the Border Trade Area (BTA) will pay attention to the Declaration of Liberal Democration Principles concerning Ethnoculture and National Minority and Native Tribes suggesting the local government to accept, with domestic laws and with the covenant legalized internationally concerning the principles of minority rights implementation, equal in its interests with the classical Human Rights.